2009
DOI: 10.1098/rspb.2008.1669
|View full text |Cite
|
Sign up to set email alerts
|

Can parasites drive population cycles in mountain hares?

Abstract: Understanding the drivers of population fluctuations is a central goal of ecology. Although well-established theory suggests that parasites can drive cyclic population fluctuations in their hosts, field evidence is lacking. Theory predicts that a parasite that loosely aggregates in the host population and has stronger impact on host fecundity than survival should induce cycling. The helminth Trichostrongylus retortaeformis in the UK's only native lagomorph, the mountain hare, has exactly these properties, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…It emphasizes the necessity to integrate parasitism, even by seemingly inconspicuous fleas, in studies involving the life-history traits of small mammals. Macroparasites as well as microparasites can affect survival and life Flea infestation reduces host life spanspan (Burthe et al 2008) and this may in turn affect population dynamics (Deter et al 2008 ;Townsend et al 2009). All manipulations were done under control of the Vaud Veterinary Authorities, authorization 1848.…”
Section: Discussionmentioning
confidence: 99%
“…It emphasizes the necessity to integrate parasitism, even by seemingly inconspicuous fleas, in studies involving the life-history traits of small mammals. Macroparasites as well as microparasites can affect survival and life Flea infestation reduces host life spanspan (Burthe et al 2008) and this may in turn affect population dynamics (Deter et al 2008 ;Townsend et al 2009). All manipulations were done under control of the Vaud Veterinary Authorities, authorization 1848.…”
Section: Discussionmentioning
confidence: 99%
“…The geohelminth T. retortaeformis has commonly been reported to parasitize lagomorphs from Spain. Several studies revealed the influence of parasitism by trichostrongilid species on host population dynamics of species of the genus Lepus (Newey et al, 2005;Townsend et al, 2009). The only available data on species of the genus Trichostrongylus parasitizing Iberian hares in southern Spain are Table 7.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of parasitological studies on southern Spain, where L. granatensis is particularly abundant. Parasitological studies have proved to be useful in the elucidation of biological features related to lagomorphs (Newey & Thirgood, 2004;Newey et al, 2005;Eira et al, 2007;Townsend et al, 2009). In the case of the Iberian hare, the only study of such characteristics is that by Alzaga et al (2008), who analysed the relationship between parasite burdens and its ability to escape from predators.…”
Section: Introductionmentioning
confidence: 99%
“…Diseases such as pseudotuberculosis, brown hare syndrome, pseudococcis and gastrointestinal parasites have been argued to also play a role in explaining population dynamics (Newey & Thirgood 2004) or fitness of adult hares (Couch et al 2012). For other hare species, it has been shown that parasites and diseases cannot sufficiently explain demographics in mountain hares (Haerer et al 2001;Frölich et al 2007;Townsend et al 2009) and snowshoe hares (Murray et al 1998), but do seem to affect body condition and nutritional status.…”
Section: Introductionmentioning
confidence: 97%
“…Studies that focused on mountain hare (Lepus timidus) population dynamics in natural areas have emphasized top-down factors such as predators and diseases (Newey & Thirgood 2004;Newey et al 2007;Townsend et al 2009). Similarly, studies on population cycles in snowshoe hares (Lepus americanus) in boreal Canada have indicated predation as the key limiting factor causing these fluctuations (for a review, see Krebs 2011), whereas climate change may lead to the disappearance of these cycles (Yan et al 2013).…”
Section: Introductionmentioning
confidence: 99%